2017
DOI: 10.1111/myc.12605
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus sensitisation in bidi smokers with and without chronic obstructive lung disease

Abstract: Recent studies have described fungal sensitisation in patients with chronic obstructive pulmonary disease (COPD). However, no study has evaluated fungal sensitisation specifically in bidi smokers. Herein, we evaluate the prevalence of Aspergillus sensitisation in bidi smokers. Bidi smokers with and without COPD underwent chest radiography, spirometry, Aspergillus skin test, A. fumigatus precipitins, A. fumigatus-specific IgE and total IgE. Aspergillus sensitisation was defined as the presence of either immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…These results are in line with previously reported data of prevalence between 8.5% and 16%. 6 , 7 , 33 , 34 As these studies are lacking an appropriate control group, our data clearly establish that sensitization to A fum is more common in COPD. We are aware of the younger age in our control group, but a median age difference of only 5 years seems insufficient to explain the higher rate of sensitization in COPD.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These results are in line with previously reported data of prevalence between 8.5% and 16%. 6 , 7 , 33 , 34 As these studies are lacking an appropriate control group, our data clearly establish that sensitization to A fum is more common in COPD. We are aware of the younger age in our control group, but a median age difference of only 5 years seems insufficient to explain the higher rate of sensitization in COPD.…”
Section: Discussionsupporting
confidence: 61%
“…This is in contrast to a recent paper about bidi smokers where current smoking seemed a risk factor for A fum sensitization, irrespective of the presence of COPD. 34 Despite similar disease severity, bronchiectasis was significantly more frequent in sensitized patients, particularly when sensitized to rAsp f1 or rAsp f3 (50% or 60% prevalence, respectively). Moreover, multivariate analysis showed that the associated risk for bronchiectasis was independent of gender, age, BMI, diffusion capacity, frequent exacerbations and presence of PPM.…”
Section: Discussionmentioning
confidence: 88%
“…We are constantly exposed to a wide range of environmental (both outdoor and indoor) mould and the consequences and implications of this in the context of chronic lung disease have been unclear. In southeast Asia, use of local hand-rolled cigarettes or "bidi" has been additionally shown to increase rates of fungal sensitisation in COPD [18]. This study highlights the association of fungal sensitisation to outdoor and indoor mould and increased severity of disease.…”
Section: @Erspublicationsmentioning
confidence: 64%
“…ABPA has been reported in other pulmonary disorders including bronchiectasis 164 , post-tubercular lung disease 165 166 , Kartagener's syndrome 167 , Macleod's syndrome 168 , chronic obstructive pulmonary disease 169 170 171 , chronic granulomatous disease and hyper-IgE syndrome 172 . Larger observations are required to establish a definite association and clinical significance.…”
Section: Abpa In Special Situations and Related Conditionsmentioning
confidence: 99%